Implementation of Creativity Media for Mathematics, Science, and Technology in Early Childhood Education During Flood Periods at Ra Al Huda Kayen Pati - Hidayah, Isti; Pranoto, Yuli Kurniawati Sugiyo; Elyana, Luluk (Universitas Negeri Semarang, 2024)
Flood periods require special attention, particularly in affected areas such as Pasuruhan Village, Kayen, Pati, which experiences annual flooding. This event disrupts public facilities, including education services. RA Al Huda faced a two-month hiatus in learning activities during the flood, leaving early childhood students (ages 4–6) to play at home without structured learning. Creativity in teaching mathematics, science, and technology (MST) for early childhood education became a critical innovation in a community service program under the KOSABANGSA 2024 initiative by DRTPM Kemendikbudristek. This program was implemented by the Universitas Ivet team in collaboration with Universitas Negeri Semarang as the advisory team. The initiative aims to develop learning media to sustain education during floods. The implementation strategy involves management and social empowerment aspects, including flood-period management for early childhood education, parenting programs, and partnerships with parents. The development of this community service project follows the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The study sample consists of the principal and teachers of RA Al Huda Pasuruhan, Kayen, Pati, along with parents. The innovation was validated by experts, achieving a score of 3.59 in the